Obeying the rules at home, playing the status game at school - Hermannsdottir, Audur; Luomala, Harri; Leipamaa-Leskinen, Hanna (Emerald, 2026)
Purpose This study aims to compare the normative influence of parents at home and peers at school on healthy eating among children aged 6–15 years, focusing on fish consumption. It distinguishes between descriptive and injunctive norms and examines whether age moderates these influences. Design/methodology/approach A sample of Icelandic children (n = 743) aged 6–15 years completed a self-administered questionnaire, enhanced with a speech synthesizer and pictorial response options to support independent participation. The survey measured fish consumption frequency at home and in school, perceived parental and peer descriptive and injunctive norms and demographic variables including age. Findings The influence of descriptive and injunctive norms on fish consumption varied based on settings. At home, parental injunctive norms had a stronger effect than descriptive norms, suggesting that children are more motivated by perceived parental expectations than by modeled behavior. In school, the reverse was true, where peer descriptive norms were influential but peers’ injunctive norms were not, indicating that school consumption is shaped by peers’ behavior but not by perceived social approval. Including age as a moderator revealed a different picture: age did not moderate parental influence at home, but it significantly moderated peer influence at school, where younger children responded more to descriptive norms, while adolescents were more influenced by injunctive norms. Originality/value The study provides new insights into how normative influences vary by context and children’s developmental stage. These insights have implications for designing age-sensitive and context-specific messages to promote healthy eating among children and adolescents.
Keywords: Fish consumption; Children; Age; Social norms; Parents; Peers; Home; School; fi=Markkinointi|en=Marketing|